2011
DOI: 10.4161/isl.3.5.15944
|View full text |Cite
|
Sign up to set email alerts
|

RFX6 is needed for the development and maintenance of the β-cell phenotype

Abstract: Extensive research is needed to specify this role and explore its significance in the efforts to treat diabetes with medications, or more importantly, through β-cell replacement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 18 publications
0
5
0
1
Order By: Relevance
“…When ranked by their correlation with delta fate, we identified Map2k4, Msi1 and Nefl as novel candidate regulators. Msi1 is regulated by Rfx4 54 , which is a paralog of Rfx6 that is structurally related to Rfx3 55 , both of which are involved in endocrine differentiation 50,5660 .…”
Section: Resultsmentioning
confidence: 99%
“…When ranked by their correlation with delta fate, we identified Map2k4, Msi1 and Nefl as novel candidate regulators. Msi1 is regulated by Rfx4 54 , which is a paralog of Rfx6 that is structurally related to Rfx3 55 , both of which are involved in endocrine differentiation 50,5660 .…”
Section: Resultsmentioning
confidence: 99%
“…By quantitative real-time PCR, pancreatic RFX6 expression is limited to adult human islet cells, and autosomal recessive mutations at this locus result in neonatal diabetes, with absence of insulin + , glucagon + , and somatostatin + cells [50,51]. Similarly, Rfx6 -deficient mice exhibit impaired formation of all endocrine cell types except for pancreatic polypeptide [50].…”
Section: Endocrine Cell Specificationmentioning
confidence: 99%
“…Although Rfx6 is expressed more broadly and earlier than Ngn3 during mouse development, Rfx6 expression is not detected in Ngn3 −/− mice. Interestingly, human NGN3 mutations result in milder diabetes cases than RFX6 mutations [51]. Thus, RFX6 could act either upstream or downstream of NGN3 in coordinating the production of a subset of islet cell types [50,51].…”
Section: Endocrine Cell Specificationmentioning
confidence: 99%
“…There are studies showing the involvement of this gene in the differentiation of islet cells and regulation of transcription factors involved in beta cell function thereby affecting insulin production [4]. Mitchell-riley syndrome is considered to be an association of a particular phenotype of Martinez-frias syndrome, and it was suggested that both represent an RFX6 malformation complex [5,6]. The expression of RFX6 gene starts early in embryonic development throughout the anterior endoderm and later on is confined to the gut and pancreas endocrine cells [1,7].…”
Section: Discussionmentioning
confidence: 99%